Economic Transformation and Income Distribution : Some Evidence From the Baltic Countries - Weder, Beatrice (IMF Working Papers; Working Paper ;, 1996)
A transition from a centrally planned to a market economy implies a massive reallocation of resources requiring realignments in relative prices, which may have important distributional effects. This paper examines the extent to which income differentials have changed in countries where bold reforms have been introduced. Discussing the experience in the Baltic states, it finds that-largely due to a significant increase in the dispersion of earnings-recorded income differentials in these countries have widened markedly and that the redistributive effects of social assistance and tax policies have been only marginal.